Dukungan Agroindustri Komoditi Andalan Perkebunan Terhadap Kinerja Perdagangan Kabupaten Aceh Timur - Ramayana Ramayana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. System of agro-industry in Aceh still rests on the upstream industry prime commodity-based plantation. In the case of agro-industry very decisive contribution to the plantation subsector in Aceh Timur GDP. This research use simulations to support export by Kuala Langsa Port. The analysis showed that several centers of raw materials production is very sensitive to a decrease in productivity of commodity areas. Based on the performance of the agro-industry coefficients for each commodity, the biggest are: animal feed industrial, cocoa and spices industry. While the industry as cocoa, coconut, turmeric and cloves are relatively small, but still larger than one. Therefore, agro-industrial system capable of providing added value to the trading system still relies on the east coast region of Aceh, Kuala Langsa ports should be developed.